The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ans.16115
|View full text |Cite
|
Sign up to set email alerts
|

Time to surgery and transfer‐associated mortality for hip fractures in Western Australia

Abstract: This study evaluated hip fracture transfer times, delays to definitive surgery affecting mortality and the negative impact of patient transfer on outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
5
1
1
Order By: Relevance
“…In our large study of NSW people with hip fractures, we found that transfer from non‐operating to operating hospitals, after adjusting for patient and hospital characteristics, was not associated with higher 30‐day mortality, despite increasing the time between initial presentation and surgery. This is contrary to the findings of earlier, single centre studies in Australia 4‐6 . However, our study was the first to control for several key person‐level factors that increase the risk of death, and our findings suggest that time to surgery may be less important for health outcomes than these factors when other dimensions of care quality are equal.…”
contrasting
confidence: 99%
“…In our large study of NSW people with hip fractures, we found that transfer from non‐operating to operating hospitals, after adjusting for patient and hospital characteristics, was not associated with higher 30‐day mortality, despite increasing the time between initial presentation and surgery. This is contrary to the findings of earlier, single centre studies in Australia 4‐6 . However, our study was the first to control for several key person‐level factors that increase the risk of death, and our findings suggest that time to surgery may be less important for health outcomes than these factors when other dimensions of care quality are equal.…”
contrasting
confidence: 99%
“…There have been no large-scale or long-term observational studies reviewing time to surgery based on regions within WA. One smaller study looking at a single institution found a 12-hour delay to surgery in patients that required an inter-hospital transfer which was associated with increased mortality [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interhospital transfer is an independent predictor of mortality in surgical patients, 17,18 regardless of time to surgery or number of comorbidities, 19,20 which is associated with increased complications, duration of stay, treatment costs and places greater demand on clinical resources than direct admissions from the emergency department. [21][22][23][24] By extension, any delays in patient transfer lead to further delays with surgery and result in longer inpatient stay.…”
Section: Introductionmentioning
confidence: 99%